HISTORIOGRAPHY OF SUNNI AND SHIAH IN THE BOOK: "WRITING AND COLLECTION OF HADITHS" BY RASUL JA'FARIYAN - Muhammad; Nazahah Najiyah, Nur Laili Nabilah (Al-Bayan: Journal of Hadith Studies, 2023)
Among the major Islamic sects that display such striking differences regarding the history of writing and bookkeeping of hadiths are Sunnis and Shias. Sunnis are of the view that the official writing of hadith began in the second century of hijrah. Meanwhile, in Shia literature, the writing of hadith was actually done during the Prophet's lifetime. Therefore, this paper will try to analyze the form of hadith historiography in the book 'Writing and Collection of Hadith' by Rasul Ja'fariyan. Therefore, there are three problem formulations; first, how is the genealogy of hadith historiography; second, how is the historicity of Shia and Sunni hadiths in the book of Rasul Ja'fariyan; and third, what is Ja'fariyan's view in assessing the historical flow of Sunni hadith writing from a Shia perspective. This paper is qualitative research with the primary data source, namely the book 'Writing and Collection of Hadith' by Rasul Ja'fariyan. Secondary data is in the form of books, journals, and research related to the historicity of Shia and Sunni hadiths. The results are, first, essentially the term historiography was born long before the 15th century. Therefore, the history of hadith needs to be written down so that it is known as "hadith historigraphy", covering its inception and development, narration, issues of sanad-matan, to the classification of the eras of the compilation of hadith books. Second, the tradition of writing hadith among Shiites has been increasingly intense since the 3rd century Hijri. While among Sunnis, the tradition of writing hadith officially has not yet received special attention, at which time the oral tradition was increasingly popular in transmitting hadith. Third, Rasulullah Ja'fariyan believes that Sunni scholars should not see the hadiths prohibiting the writing of hadiths as a legitimacy, which he sees as a factor of "delay" in the tradition of writing hadiths when compared to Shias.